(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This article analyzes the moral and educational significance of the stories of the Holy Quran. In particular, the struggle between good and evil is highlighted through the example of stories related to the creation of Adam, Iblis’s disobedience to Allah and his attempt to lead people astray. The article reveals the negative influence of Satan in human life, the religious and moral foundations of resisting his temptations, and the role of Quranic teachings in human perfection and spiritual upbringing. It also describes moral conclusions that encourage believers to be patient, pious, prayerful, and obedient to the commandments of Allah.